Aortic invovement in fibromuscular dysplasia. 3-dimensional CT, case-control study. THE ARCADIA-POL BIS study. (25th November 2020) - Szkamruk, K; Kruk, M; Kepka, C; Adlam, D; Persu, A; Canning, C; Pappaccogli, M; Van Der Niepen, P; Januszewicz, M; Kabat, M; Warchol-Celinska, E; Prejbisz, A; et al.
Abstract: Background: Fibromuscular dysplasia (FMD) is a non-atherosclerotic arterial disease that manifests as the presence of beaded or focal lesions in medium or small-sized arteries and may also include arterial dissection, aneurysm, and tortuosity. FMD could be revealed in various manifestations, however limited data on the involvement of the thoracic aorta is reported. Purpose: To measure and evaluate involvement of thoracic aorta in patients with FMD. Methods: We analysed aortas of 144 consecutive patients (mean age 50.2±14.0, 116 women) with confirmed FMD in at least one vascular bed. The control group consisted of 144 (mean age 50.5±14.0, 116 women) age and sex matched individuals. All patients underwent detailed clinical evaluation including angio-CT scan including aortic valve, thoracic aorta and coronary arteries. We measured the aortic valve annulus, sinus of valsalva, sinotubular junction, the diameters of ascending and descending aorta, aortic unfolding, the height of ostium of RCA and LCA and diameter of right and left coronary artery ostia in patients with fibromuscular dysplasia and compared them to matched controls. Results: The FMD group had significantly smaller dimensions of aortic valve annulus and sinus of Valsalva than control group (2.3 [2.1–2.6] vs 2.9 [2.7–3.1] p<0, 0001; 2.9 [2.7–3.2] vs 3.1 [2.8–3.3] p=0, 0011 respectively). In addition the FMD group had a significantly greater mean diameter of the ascending and the descending aorta than the control group (3.1 [2.7–3.3] vs 3 [2.9–3] p=0, 0436; 2.4 [2.2–2.7] vs 2.3 [1.8–2.5] p<0, 0001 respectively). The height of the ostium of the left and of the right coronary artery was smaller in FMD than in the control group (1.2 [1.1–1.4] vs 1.3 [1.2–1.4] p=0, 0001; 1.1 [1–1.3] vs 1.3 [1.1–1.4] p<0, 0001 respectively). There was no difference in the diameter of sinotubular junction and the right and the left coronary artery ostias between the FMD and control groups (2.7 [2.5–2.9] vs 2.7 [2.5–2.9]; 0.3 [0.2–0.3] vs 0.3 [0.2–0.3]; 0.3 [0.3–0.3] vs 0.3 [0.3–0.4] respectively). Conclusions: Patients with fibromuscular dysplasia display smaller dimensions of aortic valve and larger diameter of ascending and descending aorta as compared to control subjects. Despite the predominant clinical significance of focal pathologies in FMD patients, the disease may display a specific, pan-vascular phenotype. Funding Acknowledgement: Type of funding source: None